English Validation of the Parental Socialization Scale—ESPA29 - Martínez, Isabel; Cruise, Edie; García, Óscar F.; Murgui, Sergio (Frontiers in Psychology, 2017)
Parenting styles have traditionally been studied following the classical two-dimensional orthogonal model of parental socialization. The Parental Socialization Scale ESPA29 is used to measure the four styles of parental socialization through the acceptance/involvement and strictness/imposition dimensions. The ESPA29 scale is a developmentally appropriate measure of parenting styles, which has been validated in several languages including Spanish, Italian, and Brazilian Portuguese. In this study, the English translation of the ESPA29 was evaluated. The objective of the work is to test the ESPA29’s structure of parenting practices with a U.S. sample measuring parenting practices using EFA and CFA. The scores of fathers’ and mothers’ behavioral practices towards their children were obtained for a sample of 911 U.S. adolescents between 14 and 18 years of age. First, the total sample was split and a Principal Components Analysis with Varimax rotation was carried out with one of the two halves. Exploratory factor analysis (EFA) showed a two-factor structure fully congruent with the theoretical model for mothers’ and fathers’ scores. Next, a confirmatory factor analysis (CFA) was calculated on the second half by using the factor structure obtained in the previous EFA. The CFA replicated the two-factor structure with appropriate fit index. The seven parenting practices that were measured loaded appropriately on the acceptance/involvement and strictness/imposition dimensions. Then, the multigroup analysis between girls and boys showed equal loading in the factors and equal covariation between the acceptance/involvement and the strictness/imposition dimensions. Additionally, the two dimensions of the ESPA29 scale were related to self-esteem in order to obtain an external validity index. The findings confirm the invariant structure of the ESPA29 was in the United States and their equivalence in both fathers’ and mothers’ scores. These findings validate the instrument and confirm its applicability in cross-cultural research on parenting practices and child adjustment.